Morphological and production characters of Alencar and Ecuador black pepper clones cultivated in Tomé Açú, State of Pará (Research, Society and Development, 2022)
The cultivation of black pepper in live tutor of gliricidia is an alternative to the use of a wooden stake for pipericulturists. However, the adoption of this technology is limited due, among other factors, to the scarcity of information on the behavior of cultivars of the species in this type of tutor. This work focused on the comparative study of the Alencar cultivar of black pepper in gliricidia and wooden stake, comparing it with the cultivar Ecuador only for gliricidia. The experiment was carried out in a producer area in Tomé Açu - PA, with four plants per cultivar being evaluated. Plant height, stem diameter and number of orthotropic branches, petiole and leaf length, width and thickness of adult leaves, as well as size, weight and number of fruits per spike were evaluated. After ANOVA, the 5% Tukey test was followed. Regarding plant structure and leaf dimensions, there was no difference for Alencar in the two types of tutors, but this one showed greater stem diameter, leaf length and petiole than Ecuador. However, the weight of the spikes was higher in wood stake for Alencar, requiring further studies focusing only on the production of the cultivar in a comparative way using the two tutors.